Shakespeare and Chekhov in production and reception : theatrical events and their audiences - Tulloch, John (Studies in theatre history and culture., 2005)
With a focus on the canonical institutions of Shakespeare and Chekhov, John Tulloch brings together for the first time new concepts of ""the theatrical event"" with live audience analysis. Using mainstream theatre productions from across the globe that were highly successful according to both critics and audiences, this book of case studies--ethnographies of production and reception--offers a combined cultural and media studies approach to analyzing theatre history, production, and audience. Tulloch positions these concepts and methodologies within a broader current theatrical debate between page